2017
DOI: 10.1007/s10545-017-0042-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical validity of biochemical and molecular analysis in diagnosing Leigh syndrome: a study of 106 Japanese patients

Abstract: Leigh syndrome (LS) is a progressive neurodegenerative disorder of infancy and early childhood. It is clinically diagnosed by typical manifestations and characteristic computed tomography (CT) or magnetic resonance imaging (MRI) studies. Unravelling mitochondrial respiratory chain (MRC) dysfunction behind LS is essential for deeper understanding of the disease, which may lead to the development of new therapies and cure. The aim of this study was to evaluate the clinical validity of various diagnostic tools in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
102
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 86 publications
(107 citation statements)
references
References 32 publications
5
102
0
Order By: Relevance
“…In the present study, the genetic complexity of 17 different nuclear and mitochondrial genes was identified. Genetic defects associated with complex I deficiency were the most frequent, with a total diagnostic yield of 64.5% (40/62 families) . These included six mitochondrial genes in 18 families, including MTATP6 , MTND3 , MTND6 , MTND5 , MTND1 , and MTTK , in descending order of frequency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the genetic complexity of 17 different nuclear and mitochondrial genes was identified. Genetic defects associated with complex I deficiency were the most frequent, with a total diagnostic yield of 64.5% (40/62 families) . These included six mitochondrial genes in 18 families, including MTATP6 , MTND3 , MTND6 , MTND5 , MTND1 , and MTTK , in descending order of frequency.…”
Section: Discussionmentioning
confidence: 99%
“…However, following the first report on LS, patients with atypical presentations have been noted, expanding the clinical spectrum of the disorder. Likewise, the genetic spectrum has been broadened by advances in genomic technology, such as next‐generation sequencing (NGS) . Along with clinical diversity and overlapping features, genetic heterogeneity complicates the molecular diagnosis of LS.…”
Section: Introductionmentioning
confidence: 99%
“…All currently identified ECHS1D patients have mutations in both ECHS1 alleles, indicating autosomal recessive inheritance, with many different mutations identified (Table ). Patients who are homozygous for mutations in ECHS1 have all been offspring of consanguineous relationships, resulting in two copies of the same rare mutation .…”
Section: Echs1 Deficiencymentioning
confidence: 99%
“…Short‐chain enoyl‐coA hydratase (ECHS1) is a key enzyme involved in mitochondrial fatty acid ÎČ‐oxidation (FAO). Since its initial identification in 2014, 46 patients have been described with ECHS1 deficiency (ECHS1D) . Almost all of these patients have been diagnosed with Leigh syndrome (LS), a lethal form of subacute necrotizing encephalomyelopathy.…”
mentioning
confidence: 99%
“…We performed targeted gene panel of nuclear genes and mitochondrial genes that are listed in a previous publication 3 using DNA extracted from blood samples obtained from the family with GAIIx and MiSeq (Illumina, San Diego, CA) paired-end reads. 4 Notably, this patient was one of those whose targeted gene panel was sequenced previously using a detailed protocol, including variant calling. 5 The targeted gene panel sequencing detected no previously reported pathogenic variants that were considered as causative for cardiomyopathy.…”
Section: Casementioning
confidence: 99%